2018
DOI: 10.1016/s1474-4422(18)30203-5
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy with optional graded exercise therapy in patients with severe fatigue with myotonic dystrophy type 1: a multicentre, single-blind, randomised trial

Abstract: The European Union Seventh Framework Programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
106
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 36 publications
3
106
2
1
Order By: Relevance
“…However, due to differences in instrument versions, this point estimate is not easily comparable to our data. Finally, the DM1‐Activ C was the primary outcome measure in the OPTIMISTIC clinical trial, but no scale data were published except for differences in total scores between examined interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to differences in instrument versions, this point estimate is not easily comparable to our data. Finally, the DM1‐Activ C was the primary outcome measure in the OPTIMISTIC clinical trial, but no scale data were published except for differences in total scores between examined interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Since its development, the DM1-Activ C has been employed as part of a few studies, 11,12 and the instrument was also included in a recently completed multi-national trial in DM1 (ie the OPTIMISTIC trial). 13 However, to date, no study has reported results from the DM1-Activ C beyond summary point estimates of mean instrument scores. Accordingly, the objective of this study was to investigate the impact of DM1 on activities of daily living as recorded using the DM1-Activ C in patients with DM1 from the UK.…”
Section: Introductionmentioning
confidence: 99%
“…For example, despite worsening Muscular Impairment Rating Scale (MIRS) outcomes, Peric et al [17] found that total INQoL scores, as well as several subscale scores, improved over the course of 6 years. Moreover, in a recent multicentre, single-blind, randomised trial, Okkersen et al [20] identified no significant changes in total INQoL scores at 10 months from baseline between patients with DM1 receiving cognitive behavioural therapy plus standard care and optional graded exercise and those receiving standard of care alone, despite significant changes in the main endpoint (i.e. the DM1 activity and participation scale for clinical use [DM1-Activ C ]) and other secondary endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Third, due to the observational nature of our data, we were unable to draw conclusions regarding causality. Concerning interpretation of results, it is also worth pointing out that we were unable to adjust our estimates for patients’ intelligence quotient (a variable that may have an impact on how patients perceive, and are able to report of, their disease burden), and that none of the patients in our sample received cognitive behavioural or exercise therapy (which recently have proven beneficial for the capacity for activity and social participation in DM1 [20]).…”
Section: Discussionmentioning
confidence: 99%
“…There is limited literature available to evaluate the effect of exercise in individuals with myotonic dystrophy. Results from previous studies have ranged from no change from baseline to some improvement in strength and function . While informative, many prior studies have involved small numbers of subjects, and exercise regimens varied, leading to uncertainty as to which activities to recommend to patients with DM1.…”
Section: Introductionmentioning
confidence: 99%